PEMANFAATAN POTENSI WARISAN BUDAYA PURA MEDUWE KARANG DI DESA KUBUTAMBAHAN KABUPATEN BULELENG SEBAGAI TEMPAT TUJUAN PARIWISATA - Simorangkir, Elfrida (Humanis; Volume 1. No. 2. Desember 2012, 2012)
Meduwe Karang Temple in Kubutambahan Village, Buleleng Regency is one of the living monuments cultural heritage because up till now the present heritage as an tourist destination. This research focuses on potency cultures inheritance of Meduwe Karang Temple as a tourism fascination and utilization cultures tourism in Kubutambahan Village after the Meduwe Karang Temple as an cultural heritage. We can come to the conclusion that Meduwe Karang Temple still functions as a place of worship compared to long time ago as an Kahyangan Jagat Temple. It has been opened now for the public and takeshold of 21 Pura Desa as well as Subak Temple, both having a close relationship with their surrounding communities and their means of livelihood.
Keywords: Cultural heritage, tourism object